Physical activity and health-related fitness in Asian adolescents: The Asia-fit study. Issue 3 (1st February 2020) - Hui, Stanley Sai-Chuen; Zhang, Ru; Suzuki, Koya; Naito, Hisashi; Balasekaran, Govindasamy; Song, Jong-Kook; Park, Soo Yeon; Liou, Yiing-Mei; Lu, Dajiang; Poh, Bee Koon; Kijboonchoo, Kallaya; Thasanasuwan, Wiyada
ABSTRACT: Purpose : The present study aimed to investigate and compare physical activity (PA) and health-related fitness in Asian adolescents, and to examine the associations between meeting PA guidelines and attaining fitness standards. Methods : A sample of 12, 590 adolescents ( M age  = 13.63 years, SD  = 1.01) from eight Asian metropolitan cities completed measurements of PA, five field-based fitness tests, and covariates. The fitness test scores were further classified into Healthy Fitness Zone (HFZ) or Needs Improvement Zone (NIZ). Results : Findings showed that adolescents' levels of PA and fitness components differed by cities. City differences were also found in proportions of meeting PA guidelines and achieving the HFZs of aerobic capacity, muscular fitness, and body composition. After controlling covariates, meeting PA guidelines positively associated with being in the HFZs of aerobic and muscular fitness, but the association was not significant with being in the body composition HFZ. Conclusion : There was a large variation in PA and health-related fitness in adolescents across the eight Asian cities. Asian adolescents achieving PA guidelines were more likely to be in the HFZ of aerobic and muscular fitness. Prospective follow-up studies are warranted to gain better insights into the relationships between objectively-measured PA and fitness.